Solvent Extraction of Palladium(II) with 2-Ethylhexyl Benzothiazolyl Sulfide - Feng, Shaoping; Huang, Zhangjie; Xie, Mingjing (Asian Journal of Chemistry, 2012)
A new 2-ethylhexyl benzothiazolyl sulfide was synthesized and used in the extraction of Pd(II) from hydrochloric acid solution. Palladium(II) was extracted quantitatively with 2-ethylhexyl benzothiazolyl sulfide in xylene. Thiourea solution could be used as stripping agent. Extraction parameters of Pd(II), including 2-ethylhexyl benzothiazolyl sulfide concentration, contact time of aqueous and organic phases, organic/aqueous (O/A) phase ratio, thiourea concentration and hydrochloric acid concentration of aqueous phase, were studied. 2-Ethylhexyl benzothiazolyl sulfide and Pd(II) form a 2:1 adduct as Pd(EHBTS)2Cl2 in the extraction. X-ray crystal structure determination revealed Pd(EHBTS)2Cl2 square-planar complex in which 2-ethylhexyl benzothiazolyl sulfide acts as a neutral unidentate ligand coordinated with palladium(II) via the thiazolyl N atom.